Increased occurrence of brain abscesses in cirrhotic patients: A population-based 3-year follow-up study - Chen, Yen-Chun; Hung, Tsung-Hsing; Tseng, Kuo-Chih; Tseng, Chih-Wei; Hsieh, Yu-Hsi; Tsai, Chih-Chun; Tsai, Chen-Chi (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Cirrhotic patients are prone to various infectious diseases. However, it is still unknown if the occurrence of a brain abscess is associated with cirrhosis. The purpose of this study was to identify the relationship between the occurrence of a brain abscess and cirrhosis. Materials and Methods: The National Health Insurance Database, which is derived from the Taiwan National Health Insurance program, was used to collect data from 40,878 patients with cirrhosis and from 40,896 randomly selected age- and sex-matched patients. All patients were followed up to identify the occurrence of brain abscesses in 3 years. Results: A total of 143 patients (0.17%) were diagnosed with brain abscesses in the 3-year follow-up period. There were 94 (0.23%) patients with cirrhosis and 49 (0.12%) without cirrhosis (p Conclusion: Cirrhotic patients, particularly those with complicated cirrhosis, have a higher risk of the occurrence of brain abscesses than non-cirrhotic patients. Cite this article as: Chen YC, Hung TH, Tseng KC, et al. Increased occurrence of brain abscesses in cirrhotic patients: a population-based 3-year follow-up study. Turk J Gastroenterol 2017; 28: 342-6